World Tribology Congress III, Volume 2 2005
DOI: 10.1115/wtc2005-63654
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Material Sub-Surface Defects in Rolling Contact Fatigue

Abstract: To ensure the safety and of reducing the costs of maintenances in railways systems, it is necessary to evaluate the life prediction of fatigue crack initiation in rolling contact fatigue starting from the defects. The influence of defects on the rolling contact fatigue was studied, we simulated two types of geometry of defect (circular and elliptic) and also we studied the influence of defects clusters. The stresses and deformations were analyzed in the vicinity of the defect. Calculations were carried out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…15,16 The life of rolling element bearing has been defined as the time till the first fatigue spall is initiated and it has also been reported that the vibration level and heat generation increases if bearings are operated even after the initiation of a spall. 17 Analytical and experimental methods, and mathematical models which have been used for estimating fatigue life and spall propagation, [18][19][20][21][22][23] has provided important guidelines for understanding the fatigue failures in rolling bearings. Most of the researches have been focused on effect of defect size and their location, magnitude of load, oxide inclusions, and effect of texturing on rolling contact fatigue by employing experimental methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The life of rolling element bearing has been defined as the time till the first fatigue spall is initiated and it has also been reported that the vibration level and heat generation increases if bearings are operated even after the initiation of a spall. 17 Analytical and experimental methods, and mathematical models which have been used for estimating fatigue life and spall propagation, [18][19][20][21][22][23] has provided important guidelines for understanding the fatigue failures in rolling bearings. Most of the researches have been focused on effect of defect size and their location, magnitude of load, oxide inclusions, and effect of texturing on rolling contact fatigue by employing experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…20 The influence of circular and elliptical defects and their cluster on the rolling contact fatigue were studied by simulation. 21 Also, based on three-dimensional FE Models and crack initiation fatigue life of rolling contacts have been estimated. 22,23 Presence of textures at the contacts yields favorable tribological effects such as reducing the friction and improving the lubrication under boundary/mixed lubrication regimes as the micro features enhances the lubricity at the contacts even under harsh operating conditions and help in increasing the fatigue life of the contacts.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some scholars have carried out researches on rolling contact fatigue of bearings by using analytical and experimental methods. 18 All of the studies provided an important guide for exploring the rolling contact fatigue failure of bearings. Especially, it should be noted that on one hand, the large majority of the studies directly investigate the effect of surface texturing, oxide inclusions, defect size, load magnitude and defect location on rolling contact fatigue using experimental methods.…”
Section: Introductionmentioning
confidence: 99%